Description of a new early-derivative mite, Pentasetacus plicatus n. sp. (Acariformes, Eriophyoidea), and remarks on the systematic position of pentasetacines - Chetverikov, Philipp E.; Petanović, Radmila U. (Zootaxa, 2016)
A new vagrant early-derivative eriophyoid mite species Pentasetacus plicatus n. sp. (GeneBank accession number KT070291) is described from Araucaria araucana (Molina) K.Koch from Chile and Peru with the aid of conventional and confocal laser scanning microscopy. Observations on the gnathosoma of the new species indicate that the oral stylet is bent in the middle and twice shorter than the infracapitular and cheliceral stylets. A trough-like subcapitulum originated from the palpcoxae, and swollen basal parts of chelicerae bearing putative cheliceral seta, were observed under CLSM in specimens with disjointed mouth parts. Males with an exposed gonopore under an uncovered genital coverflap and remnants of soft genital organs were registered. Contrary to other eriophyoids, the plates of the longitudinal bridge in P. plicatus n. sp. and other pentasetacines are not fused so that the genital slit continues posterior to the spermathecal apparatus. The previously established taxon Pentasetacidae Shevchenko, Bagnyuk, Sukhareva, 1991 is proposed for the eriophyoids bearing five prodorsal shield setae (Loboquintus and Pentasetacus); a refined diagnosis of Pentasetacidae is given.